Remote monitoring and watering system for Red Onion Plants through Telegram based on IoT - Rahmat, Ahwal; Hastuti (Department of Electrical Engineering Universitas Negeri Padang, 2025)
Red onion (Allium cepa L.) is an important horticultural commodity in Indonesia that is vulnerable to air pollutants, especially dust and dew that can disrupt the photosynthesis process and trigger diseases such as fusarium wilt. This research aims to design a remote monitoring and watering system based on Internet of Things (IoT) using ESP32-CAM. The system automatically takes images of red onion leaves every morning and sends them to the farmer's Telegram, allowing farmers to analyze leaf conditions and activate remote watering if necessary. This system not only improves monitoring efficiency and decision-making but also reduces excessive pesticide use due to delayed handling. Thus, this system is expected to be an innovative and sustainable solution in supporting smart farming practices for red onions in highland areas. Keywords—Red onion, IoT, ESP32-CAM, Telegram, Monitoring.